Higher posts in Civil Service: Some reflections on the latest amendments - Mędrala, Małgorzata (Journal of Public Governance, 2018)
The amendment to the Act on Civil Service and other acts was passed on 30 December and entered into force on 23 January 2016. The amended Act introduced significant changes concerning recruitment for higher positions in the Civil Service. The changes may be considered controversial in many aspects, especially from a constitutional perspective. The objective of this paper is the assessment of the amendments with special focus on the principle of equal treatment, especially open and competitive recruitment for public service. Dogmatic and analytical methods were used in the paper. The Author analyzes the regulations of the amended Act, focusing on the most important changes in recruitment procedures for higher positions in Civil Service. The Author concludes that the new regulations concerning recruitment for higher positions in Civil Service violate the principle of a politically neutral and professional Civil Service.